Flame-retardant nanocoating towards high-efficiency suppression of smoke and toxic gases for polymer foam. (August 2022) - Zhang, Jia-Yan; Zhao, Hai-Bo; Zhang, Ai-Ning; Cheng, Jin-Bo; Li, Shu-Liang; Zhao, Wei; Fu, Teng; Zhao, Ze-Yong; Wang, Yu-Zhong
Graphical abstract: Highlights: An eco-friendly flame-retardant porous nanocoating has been developed for flexible polyurethane foam. The nanocoating shows the high efficiency of flame retardancy and suppression of smoke and toxic gases. The nanocoating has a little negative effect on the mechanical properties of the foam. The flame-retardant and smoke-suppression mechanism of the nanocoating has been revealed in detail. Abstract: In this study, we demonstrate an environmentally friendly and facile flame-retardant nanocoating that can effectively suppress smoke and toxic gas release in fire for flexible polyurethane foam (FPUF). In this water-based functional coating system, nanoporous sepiolite nanofibers are wrapped by phytic aid to have a negative charge, and then together with the positively charged CH, are stably deposited onto the surface of FPUF through Layer-by-Layer assembly. Only one bilayer of CH/SEP@PA coating can significantly reduce the peak heat release rate by 46%. The smoke density and the peak production of toxic CO and NOx have been greatly decreased by 77%, 52%, and 65%, and it shows an excellent extinguishing performance and easily passes the vertical burning test. Further, the nanocoating has little effect on the mechanical properties. This work provides a new strategy for the design of flame-retardant coatings with high-efficiency suppression of smoke and toxic gases for polymer foams.